An efficient time-domain prediction model for vortex-induced vibration of flexible risers under unsteady flows. (March 2019) - Lu, Ziqi; Fu, Shixiao; Zhang, Mengmeng; Ren, Haojie
Abstract: In this study, an efficient time-domain prediction model is developed to predict unsteady flow vortex-induced vibrations (VIV) of flexible risers. The hydrodynamic forces on flexible risers are calculated on the basis of forced oscillation experiments on rigid cylinders. A period identification criterion, based on the spatial and temporal variations of reduced velocity, is proposed to divide the entire vibration process into exciting and damping periods of each exited mode. In exciting periods, assuming that VIV enters an ideal lock-in stage, a non-iterative solving model is established under modal space for response calculations, which efficiently predicts time domain VIV responses. In damping periods, free-decay vibration theory based recurrence formulas are established under modal space, and they get solved stepwise for modal responses. After some slight response adjustments to smooth period transitions, the VIV response time history can be obtained efficiently. This model is validated by steady flow VIV prediction cases, and further applied to predict oscillatory flow VIV experimental results. The prediction cases reveal that this model is able to realize high-speed VIV predictions with satisfactory results and no convergence problems. This model, with high efficiency and stability, is highly suitable for unsteady flow VIV prediction in engineering applications. Highlights: An efficient time-domain prediction model is proposed for high-speed VIV predictions under unsteady flows. A period identification criterion is developed to distinguish exciting- and damping-dominant periods for each exited mode. In exciting periods, a non-iterative response solver is further developed to calculate time-domain VIV responses. In damping periods, free-decay vibration theory based recurrence formulas are established for response calculations. The model is validated by experimental results in steady flow and oscillatory flow VIV prediction cases.